Prevalence of multiple sclerosis in the South of Italy based on healthcare administrative data. (13th November 2019) - Palladino, R; Brescia Morra, V; Lanzillo, R; Giordana, R; Fumo, M G; Montuori, P; Sormani, M P; Triassi, M; Moccia, M
Abstract: Background: Multiple sclerosis (MS) is an heterogenous disease whose prevalence varies in Europe. Hereby, we aimed to estimate prevalence of MS in the Campania Region of Italy. Methods: To identify individuals with MS living in the Campania Region of Italy, we extracted data from the following healthcare administrative databases: hospital discharge records, regional drug registry, and specialist outpatient visits from Jan-2015 to 3Dec-2017. Individuals alive on the 1-Jan-2018 were included to capture prevalence on this date. Age-sex standardised prevalence rates were calculated using the direct standardisation method; the European population in 2018 was considered as reference population. To assess differences in the prevalence ratios across the five provinces of the region, standardised morbility ratios (SMR) were calculated. To calculate 95% confidence intervals (95%CI) for the standardised rates, the Byar's approximation method based on the Poisson distribution was used. Results: We identified 5, 361 individuals with MS (females 64.5%, age 45.6±12.7 years). Standardised prevalence rate per 100, 000 people was 90.0 cases (95%CI=87.60, 92.40) (112.07 for females [95%CI=108.36, 115.88] and 66.20 for males [95%CI=63.26, 69.25]). The SMR in the province of Naples, the most densely populated, was 0.90 (95%CI=0.86, 0.96), whereas the highest SMR was found in the province of Salerno (SMR=1.30; 95%CI=1.23, 1.38), and the lowest in the province of Caserta (SMR=0.89; 95%CI=0.82-0.96). Conclusions: Prevalence of MS in the Campania Region is lower than previous estimates from smaller areas in the North of Italy, suggesting a longitudinal gradient. Differences within the Region could be explained by genetic/environmental background and healthcare organization (e.g., missing diagnoses). In the future, healthcare administrative databases could be used to monitor MS prevalence/incidence and to plan healthcare resource utilization. Key messages: Prevalence of MS in the Campania Region is 90 cases per 100, 000 people. It is lower than previous estimates from smaller areas in the North of Italy, suggesting a longitudinal gradient. Differences within the Region could be explained by genetic/environmental background and healthcare organization (e.g., missing diagnoses).